PENGARUH GAYA HIDUP DAN MOTIVASI TERHADAP KEPUTUSAN MENJADI MAHASISWA - Daniel (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
The purpose of this study was to determine the correlation between motivation and lifestyle on the decision to become a student at a university. The research method used is a quantitative method with a collection technique in the form of distributing questionnaires. The results of the study found that there was a positive and significant influence between lifestyle and motivation on the decision to become a student.